EVALUASI INSTALASI POMPA AIR TENAGA SURYA DI INDONESIA DENGAN MENGGUNAKAN STANDAR IEC 62253-2011 - Danar Agus Susanto; Utari Ayuningtyas; Hermawan Febriansyah; Meilinda Ayundyahrini (JURNAL STANDARDISASI, 2018)
Water pumps using solar power have been widely applied in Indonesia, especially in remote areas with limited power and the difficulty of fuel oil. Installation of PATS for remote areas is very beneficial, both socially, economically and environmentally. However, PATS installed can not maximize its efficiency even can experience problems and system failures when installed, used and maintained not in accordance with the procedure. The International Electrotechnical Commission (IEC) has established the IEC 62253-2011 standard on Photovoltaic pumping systems - Design qualification and performance measurements. This standard can be used as guidance and procedure in PATS installation system, so the problems in PATS can be minimized. The purpose of this research is to mapping the problem of installation of PATS by using parameters in standard IEC 62253-2011. This research uses gap analysis method to find the gap between PATS installation in Indonesia with standard parameter of IEC 62253-2011. The result of research through gap analysis indicate that 51% aspect in IEC 62253-2011 is not fulfilled by user which enable decrease efficiency even PATS system failure, although actually all parameters in the IEC 62253-2011 standard may be possible. The biggest aspect that is not met is related to the availability of operating and maintenance handbook for the pump maintenance staff at the PV pumping site and maintenance handbook covering operation, repair and servicing. This makes it possible for operator ignorance to install, operate and maintain the system, so that human error becomes the most dominant factor in PATS system application. The PV generator becomes the product aspect that most not complies with standard with percentage of 71%, although there are 22 SNI about PV covering module, installation, testing and construction.